Ultra-high Voltage AC/DC Power Transmission (Advanced Topics in Science and Technology in China,, 2018)
This book addresses the latest findings on practical ultra-high voltage AC/DC (UHVAC/UHVDC) power transmission. Firstly, it reviews current constructions and future plans for major UHVDC and UHVAC projects around the world. The book subsequently illustrates the basic theories, economic analysis, and key technologies of UHV power networks in detail, and describes the design of the UHVAC substations and UHVDC converter stations and transmission lines. A wealth of clear and specific figures and formulas help readers to understand the fundamental theories underlying UHVAC and UHVDC technologies, as well as their developmental trends. This book is intended for graduate students, researchers and engineers in the fields of power systems and electrical engineering.